Thermoregulatory development and behavior of Ctenomys talarum pups during brief repeated postnatal isolation - Baldo, María Belén (2014)
In altricial mammals, the role of the mother and siblings throughout pup's early ontogeny is critical to determine “normal” development in neonates. It has been reported that variations in parental investment during pups' development affect thermoregulatory capacity, growth patterns, brain development and behavior during lifetime, such as spatial learning and memory in adults. Ctenomys talarum (tuco-tuco) is a solitary subterranean rodent, who inhabits complex burrows and exhibits developed spatial orientation abilities. Tuco-tuco's pups display an altricial development, spending more than 80% of the time in contact with the mother. Throughout weaning period, pups display active exploratory behavior and improvements in their spatial capabilities. Then, we determined the effect of repeated brief postnatal isolations on the acquisition of physiological thermoregulation and the development of spatial learning capabilities in tuco-tuco's pups. As it occurs in wild animals, daily brief isolations (30 min) did not affect the acquisition of adult's body temperature nor resting metabolic rate's development pattern. Moreover, behavioral response and adult spatial abilities of isolated pups were similar to that observed in non-isolated ones. Then, during periods of mother's absence, minor physiological and behavioral adjustments, such as shivering and postural changes, are required to keep C. talarum pups within allostasis.